توظيف التراث السردي في الرواية الجزائرية من خلال الإطار الحكائي (الف ليلة ليلة ) - بن يطو, عبد الرحمن (Université de M'sila, 2017)
Arabian Nights is considered one of the most widespread narrative works in the world, because of it special features and its eternal qualities, like the magical nature of events, the innovative way of narration, that’s why a lot of poets and writers were inspired by its multiple meanings and hidden connotations. Among those who were inspired there are some Algerian novelists, like Abd Elmalek Mortadh in the novel “the pigs” and Rachid Boudjedra in “A thousand and one year of nostalgia” and Abd Elhamid Ben Hadouga in “Tomorrow is a new day” and Wassini Al Aaradj” in his novel “The trajedy of the seventh night after the the thousand- El Maya sand.” Arabian Nights became a source of inspiration in knowledge whether in the way of heritage narration or in the narratological framework of the novel.